2018
DOI: 10.1080/13803395.2018.1501001
|View full text |Cite
|
Sign up to set email alerts
|

Facial expression recognition in Alzheimer’s disease: A systematic review

Abstract: The lack of standardized assessment instruments and the heterogeneity of the methods and samples used across studies hamper comparisons. Future researches should investigate facial expression recognition through more ecological and standardized methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…All participants recognized the joy emotion of music, followed by sadness emotion, but the fear emotion seemed more difficult to recognize from the music pieces by all groups. Fear is a very complex emotional expression and several studies also observed similar results for fear emotion recognition vs. joy and sadness emotions from faces [29, 40, 46]. Recognition impairments for facial expressions of emotion are seen in AD [27, 28] and more altered in semantic dementia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…All participants recognized the joy emotion of music, followed by sadness emotion, but the fear emotion seemed more difficult to recognize from the music pieces by all groups. Fear is a very complex emotional expression and several studies also observed similar results for fear emotion recognition vs. joy and sadness emotions from faces [29, 40, 46]. Recognition impairments for facial expressions of emotion are seen in AD [27, 28] and more altered in semantic dementia.…”
Section: Discussionmentioning
confidence: 90%
“…Recognition impairments for facial expressions of emotion are seen in AD [27, 28] and more altered in semantic dementia. Nevertheless, some studies [4, 46] found unimpaired performances in recognition of non-familiar facial and non-familiar musical emotions in AD.…”
Section: Discussionmentioning
confidence: 99%
“…In the review by Fittipaldi et al(23), the relationship between primary progressive aphasia (PPA), FTD subtype, and de cits in areas and sub-areas of SC such as the theory of mind, emotion recognition or empathy cannot be precisely assert for PPA as a whole; instead, speci c links are recognized for each variant. On the other hand, Torres Mendonça De MeloFádel et al (24),studied the relationship between emotional recognition and Alzheimer's disease, without a consistent conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…PwD may have emotion processing deficits in several domains, along with their cognitive deficits, for example reduced perception of emotional facial expressions (Hoffmann et al, 2010;Klein-Koerkamp et al, 2012a,b;Kumfor et al, 2014). This ability plays a significant role in communication and is one of the most important aspects of social cognition (León et al, 2011;Torres et al, 2015;Torres Mendonça De Melo Fádel et al, 2018). Social cognition allows individuals to partake in social situations, enabling them to perceive and recognize the thoughts, emotions, and behaviors of others (Shany-Ur and Rankin, 2011).…”
Section: Introductionmentioning
confidence: 99%